Faktor-Faktor Yang Mempengaruhi Ekspor Kelapa Indonesia di Pasar Malaysia - Safrida Safrida; Indra Indra; Sari Darnita; Litna Ginting (JASc (Journal of Agribusiness Sciences), 2022)
Indonesia is a country with the largest coconut production in the world. Indonesias coconut exported to different countries in the world, from Asia to Europe. Indonesia's coconuts are mostly exported in neighboring countries, Malaysia which is the highest export volume compared to other export destination countries. The purpose of this research is to analyzes the Factors Affecting of Indonesian Coconut Export in Malaysian Market. The analysis period used in this research is from 2010 to 2019 with using the multiple linear regression analysis method. The variables contained in the model are Indonesian coconut production, the exchange rate of the rupiah to the dollar, the export price of Indonesian coconut, and the demand for coconut exports in Malaysia. The results of this research indicate that the variable of export price of Indonesian coconut and the exchange rate of the rupiah to the dollar have a positive effect on the volume of Indonesian coconut exports in the Malaysian market. Meanwhile, the variables of Indonesian coconut production and demand of coconut exports in Malaysia have a negative effect on the volume of Indonesian coconut exports in the Malaysian market.